LARVICIDAL PROPERTY OF SUGAR APPLE (ANNONA SQUAMOSA) AND SAN FRANCISCO (CODIAEUM VARIEGATUM) AGAINST YELLOW FEVER MOSQUITO (AEDES AEGYPTI) - Mangubat, Florieza M (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Two Philippine plants, sugar apple ( Annona squamosa ) and San Francisco ( Codiaeum variegatum ), reported having insecticidal properties were selected for investigation, Samples were screened and assayed for their larvicidal property against Aedes aegypti by exposing 3rd-4th instar larvae with a unified amount of concentrations with two solvents. Trials were performed to determine the average mortality rate of concentrations after the LD50 value to compare the larvicidal property of the two identified plants and to compare the susceptibility of Aedes aegypti . Findings of the study showed that San Francisco-chloroform obtained the highest larvicidal activity after 24 hours of exposure while atis- ethyl alcohol signified the highest larvicidal activity after 48 hours of exposure against larvae of Aedes aegypti .